The factors that influence employee retention in XYZ Company / Nurul Atiqah Baddli Shah - Baddli Shah, Nurul Atiqah (Faculty of Business and Management, 2018)
Company have to put greater effort in order to ensure their talented and skilful employees retain in the organization. One way to stay competitive in an industry or market is by taking care of their employees. This is because when employees felt great with their work, they tend to become competitive and increase their performance to help company achieve its target. There are a few employees might do not have any intention to switch to the other company or there are high switching barriers that prevent them from moving to other organisations but it is very critical for every company to identify the factors that can influence their employees to retain in the company. The objective of this study is to identify the level of critical factors which are compensation, performance appraisal and training and career development that could affect employee retention. Besides, the researcher also examines the correlation or relationship between all independent variables with the dependent variable. The researcher also identifies the factor that affects the dependent variable. In collecting data, the researcher used primary data which is questionnaire as a way to get feedback from the employee. Using convenience sampling technique, 135 respondents have participated in this study. In this research, the finding shows that all the independent variables (compensation, performance appraisal and training and career development) have positive relationship with the dependent variable (employee retention). According to regression analysis, all of the independent variables are significant. The findings of this study will be beneficial to the XYZ Company and their employees where the company can reduce their turnover rates and enhancing their retention strategy.